Diagnosis and Successful Management of an Unusual Presentation of Chronic Foot Pain Using Positron Emission Tomography/Magnetic Resonance Imaging and a Simple Surgical Procedure. Issue 1 (January 2020) - Cipriano, Peter William; Yoon, Daehyun; Holley, Dawn; Hargreaves, Brian Andrew; Carroll, Ian Richard; Curtin, Catherine Mills; Biswal, Sandip
Abstract : Abstract: A 61-year-old man presented with chronic dorsal foot pain of 9 years that worsened with ambulation. Conventional diagnostic imaging and medical workup were unrevealing, and ankle arthrodesis had been recommended by an orthopedic surgeon for pain relief. Instead, the patient participated in a clinical imaging trial designed for identifying pain generators using whole-body fluorodeoxyglucose (18F-FDG) positron emission tomography/magnetic resonance imaging (PET/MRI). The scan revealed not only high 18F-FDG uptake at the site of pain, but also a hematoma and an inflamed, fibrotic, ruptured plantaris muscle. The fibrotic plantaris likely altered biomechanics with walking, explaining why symptoms worsened with activity. A simple tenotomy of the plantaris tendon was performed to decouple ankle movement from the plantaris injury, resulting in pain relief. This case illustrates the potential of whole-body 18F-FDG PET/MRI to better localize pain generators.